Multiple antisense oligonucleotides targeted against monoacylglycerol acyltransferase 1 (Mogat1) improve glucose metabolism independently of Mogat1 - Andrew J. Lutkewitte; Jason M. Singer; Trevor M. Shew; Michael R. Martino; Angela M. Hall; Mai He; Brian N. Finck (Elsevier, 2021)
Objective: Monoacylglycerol acyltransferase (MGAT) enzymes catalyze the synthesis of diacylglycerol from monoacylglycerol. Previous work has suggested the importance of MGAT activity in the development of obesity-related hepatic insulin resistance. Indeed, antisense oligonucleotide (ASO)-mediated knockdown of Mogat1 mRNA, which encodes MGAT1, reduced hepatic MGAT activity and improved glucose tolerance and insulin resistance in high-fat diet (HFD)-fed mice. However, recent work has suggested that some ASOs may have off-target effects on body weight and metabolic parameters via activation of the interferon alpha/beta receptor 1 (IFNAR-1) pathway. Methods: Mice with whole-body Mogat1 knockout or a floxed allele for Mogat1 to allow for liver-specific Mogat1-knockout (by either a liver-specific transgenic or adeno-associated virus-driven Cre recombinase) were generated. These mice were placed on an HFD, and glucose metabolism and insulin sensitivity were assessed after 16 weeks on diet. In some experiments, mice were treated with control scramble or Mogat1 ASOs in the presence or absence of IFNAR-1 neutralizing antibody. Results: Genetic deletion of hepatic Mogat1, either acutely or chronically, did not improve hepatic steatosis, glucose tolerance, or insulin sensitivity in HFD-fed mice. Furthermore, constitutive Mogat1 knockout in all tissues actually exacerbated HFD-induced obesity, insulin sensitivity, and glucose intolerance on an HFD. Despite markedly reduced Mogat1 expression, liver MGAT activity was unaffected in all knockout mouse models. Mogat1 overexpression in hepatocytes increased liver MGAT activity and TAG content in low-fat-fed mice but did not cause insulin resistance. Multiple Mogat1 ASO sequences improved glucose tolerance in both wild-type and Mogat1 null mice, suggesting an off-target effect. Hepatic IFNAR-1 signaling was activated by multiple Mogat1 ASOs, but its blockade did not prevent the effects of either Mogat1 ASO on glucose homeostasis. Conclusion: These results indicate that genetic loss of Mogat1 does not affect hepatic MGAT activity or metabolic homeostasis on HFD and show that multiple Mogat1 ASOs improve glucose metabolism through effects independent of targeting Mogat1 or activation of IFNAR-1 signaling.